Agricultural Production, Dietary Diversity and Climate Variability - Dillon, Andrew (Taylor and Francis, 2015)
Nonseparable household models outline the interlinkage between agricultural production and household consumption, yet empirical extensions to investigate the effect of production on dietary diversity and diet composition are limited. While a significant literature has investigated the calorie-income elasticity abstracting from production, this paper provides an empirical application of the nonseparable household model linking the effect of exogenous variation in planting season production decisions via climate variability on household dietary diversity. Using degree days, rainfall and agricultural capital stocks as instruments, the effect of production on household dietary diversity at harvest is estimated. The empirical specifications estimate production effects on dietary diversity using both agricultural revenue and crop production diversity. Significant effects of both agricultural revenue and crop production diversity on dietary diversity are estimated. The dietary diversity-production elasticities imply that a 10 per cent increase in agricultural revenue or crop diversity result in a 1.8 per cent or 2.4 per cent increase in dietary diversity respectively. These results illustrate that agricultural income growth or increased crop diversity may not be sufficient to ensure improved dietary diversity. Increases in agricultural revenue do change diet composition. Estimates of the effect of agricultural income on share of calories by food groups indicate relatively large changes in diet composition. On average, a 10 per cent increase in agricultural revenue makes households 7.2 per cent more likely to consume vegetables, 3.5 per cent more likely to consume fish, and increases the share of tubers consumed by 5.2 per cent.